Identification of Pseudo-nitzchia spp. ( Bacillariophyceae) at two different locations of Kuching estuarine waters by light and electron microscopy. - Suriyanti, Su Nyun Pau (Universiti Malaysia Sarawak (UNIMAS), 2008)
Amnesic shellfish poisoning (ASP) is caused by contamination of Domoic Acid (DA) that derived from several genera of diatom, including Pseudo-nitzschia spp. In this study, distribution and abundance of Pseudo-nitzschia was determined in two estuarine water in Kuching, i. e. Santubong and Semariang Batu. Net (20µm mesh size) hauled sample were collected and preserved for identification and live sample were used for clonal culture establishment. Identification of Pseudo-nitzschia was carried out using light microscope (LM) and electron microscope (EM). Our result showed that at least 3 species of Pseudo-nitzschia was found in the water, namely P. fraudulenta, P. subpacifica and one unidentified species. Toxin analysis using AOAC mouse bioassay showed that the extract of P. fraudulenta killed mice within 24 hours. However, further toxin analysis using Iligh Performance Liquid Chromatography (HPLC) or Liquid Chromatography Mass Spectrometry (LCMS) is essential. This represents the first report of potential toxic Pseudo-nitzschia spp. in Malaysian waters.